Single particle cryo-EM structure of the outer hair cell motor protein prestin - Carmen Butan; Qiang Song; Jun-Ping Bai; Winston J. T. Tan; Dhasakumar Navaratnam; Joseph Santos-Sacchi (Nature Communications, 2022)
Prestin, expressed in outer hair cell (OHC), belongs to the Slc26 transporter family and functions as a voltage-driven motor that drives OHC electromotility. Here, the authors report cryo-EM structure and characterization of gerbil prestin, with insights into its mechanism of action.